Putting nature back in the water, energy, and food nexus : exploring opportunities to improve local livelihoods in the Kavango East Region in Namibia - Kasino, Romanus Immanuel (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021.